What knew about external fixation of distal radial fracture in thirty years? Experience and brief bibliographic review - Vivas, Mauro R. (2021)
Introduction: Fractures of the distal end of the radius are a great subject of controversy due to their great variability in radiological patterns and patient type. The radiological clinical disagreement remains unresolved which is the best method. We decided to develop our experience with external fixation and carry out a brief review on the subject. Objective: We conducted a literature search by two of the search engines more complete and updated on health about everything concerning fractures of distal radio treated with external fixators in the last 30 years. Materials and methods: A search was conducted with the acronym "fracture distal radius with fijador externo" in MEDLINE and ProQuest Health & Medical Complete where were obtained 1367 articles in total, of which 243 were selected articles. Results and conclusions: The data that we obtained were very satisfactory with regard to the treatment of fractures of the radius with external fixators, which is an undisputed method in some types of fractures, which promote the respect for the soft parts and the biological treatment of fractures not to mention the rapid rehabilitation that is achieved with the external fixator.